COP27 special edition newsletter - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
As negotiators gather for the 27th session of the Conference of the Parties to the UNFCCC (COP27), we share select events and resources related to climate justice for women and girls.